Deconstructing the impact of social media marketing within the South African trade publishing industry - Van Graan, Talita Chenet (My University, 2021)
The objectives of this study are to determine if social media marketing within the South African trade publishing industry has a measurable, direct impact on the book sales of two representative titles. Further objectives are to establish the reach, engagement and the corresponding impact on sales of social media marketing campaigns, which kinds of posts have the most impact, and which platform is the most effective. To gain a deeper understanding of this research study, theories relating to the traditional marketing mix, digital marketing, social media types, social media marketing, influencer marketing, and the South African digital-and publishing landscape are described. In order to inform these questions, quantitative research using secondary data is conducted by collecting the total lifetime social media activity for each title by means of a manual data scrape of all mentions on all three major social media platforms namely Facebook, Twitter and Instagram. These data points are manually categorised by the researcher in order to create a timeline of the social media activity for the two case studies. These results are juxtaposed to the lifetime sales data in order to establish any trends. The study replicates an existing study conducted in the United Kingdom in 2014 by Jamie Criswell and Nick Canty. The most important findings of this study indicate that the title that garnered the most social media interaction overall did not result in the most sales. While social media marketing remains an invaluable marketing tool, it is not uniformly effective for all titles. Different factors impact on the success a social media marketing campaign for a book as relating directly to sales. These contributing factors include the age and social media presence of the target audience, whether the author is active on social media, and if there is an existing, established online core audience. Instead, the real value of social media appears to be its ability to converse directly with, and exploit established communities. Social media marketing is most effective if there is an established community. While examining only two titles cannot be deemed to be representative of the entire South African publishing industry including academic-trade-and scholarly publishing, the study attempts to provide a credible starting point in understanding the measurable value of social media marketing and the corresponding impact on book sales
A research report submitted to the School of Literature, Language and Media, Faculty of Humanities, University of the Witwatersrand in partial fulfilment of the requirements for the degree of M.A. Publishing Studies by combination of coursework and research, 2021